New technology using Arduino and capacitive sensors to reduce olive oil waste in the mills operating in the Syrian coast - محمد, محمد; مخائيل سليم مخول ,; مناف محسن سليمان, (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, a system was designed to monitor the quality of olive oil production within industrial facilities to ensure quality and reduce waste in secondary outputs, as well as save time and effort in training individuals and enable consumers and producers to evaluate the oil's quality and determine the amount of waste quickly and easily without the need for complex equipment, specialized expertise, or corrective actions. To design the appropriate system, two directions were followed: the first direction includes calibration and data collection processes, while the second direction is specific to monitoring operations, data storage, and display. The proposed system represents a new method for monitoring the quality of olive oil production, as it includes a capacitor designed with specific dimensions and measurements to work with a dedicated control circuit for measuring the dielectric constant of olive oil and determining its quality (the amount of water in the oil). It also aims to reduce olive oil waste in the olive oil water generated from the mills (the amount of oil in the olive oil water) and display the results directly on the LCD display screen, in addition to the LabView display interface, which allows for displaying the measured information in an easily readable format and remote storage and monitoring. The Arduino IDE programming environment was used to program the controller. The UART communication protocol was used to achieve communication between the smart controller and the programming interface. The test results compared to the calibration values indicate that the designed system possesses speed, accuracy, and high efficiency in monitoring the quality of olive oil production.